Teaching English vocabulary using the audio-lingual method : A classroom action research conducted in class 3A SD Shalom Semarang in the academic year 2022/ 2023 - Lie Ericko Nathan; Didit Kurniadi; Ahmad Muhid; Eko Heriyanto (Universitas Aki, 2023)
Language is a system of spoken, manual (signed), or written symbols in which human beings express themselves as members of a social group and participants in its culture. The audio-lingual teaching method is defined as a method that emphasizes on repetition of words to help the students to understand the use of the target language communicatively. The objective of this thesis is to measure the students’ accomplishment in increasing their English vocabulary after using the audio-lingual method and to find the benefits of using the audio-lingual method in increasing the vocabulary for students. In finishing this research, the method used is class action research by applying mixed methods. The population of this research was students in 3A Generous of SD Shalom Semarang, which consist of 25 students. The writer used the theory of Larsen-Freeman in this research. The instrument of the research were multiple-choice tests of 15 items and short essay tests of 5 items. In finding, the score of the post-test (84,6%) is higher than the score of the pre-test (75,8%). It means that using the audio-lingual method in teaching English vocabulary gives enough effect on the third-grade students’ accomplishments.